2003
DOI: 10.1021/jp022347p
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid−Base Ionic Liquids as Proton-Conducting Nonaqueous Electrolytes

Abstract: A new series of Brønsted acid−base ionic liquids were derived from the controlled combination of a monoprotonic acid with an organic base under solvent-free conditions. Appropriate amounts of solid bis(trifluoromethanesulfonyl)amide (HTFSI) and solid imidazole (Im) were mixed at various molar ratios to have compositions varying from an equimolar salt to HTFSI- or Im-rich conditions. The mixture at equivalent molar ratio formed a protic neutral salt with a melting point of 73 °C, which was thermally stable at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
724
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 692 publications
(747 citation statements)
references
References 144 publications
21
724
1
1
Order By: Relevance
“…In case of acid or base excess compositions, the TGA curve would show a two-step process, with the initial loss corresponding to the excess of acid or base in the system. 25 Thermophysical Properties. Some representative DTA scans for protic ILs of this study are shown in Figure 3 to indicate the variety of signals that can be obtained for different cases and the manner in which the transition temperatures are defined from these signals.…”
Section: Tgamentioning
confidence: 99%
“…In case of acid or base excess compositions, the TGA curve would show a two-step process, with the initial loss corresponding to the excess of acid or base in the system. 25 Thermophysical Properties. Some representative DTA scans for protic ILs of this study are shown in Figure 3 to indicate the variety of signals that can be obtained for different cases and the manner in which the transition temperatures are defined from these signals.…”
Section: Tgamentioning
confidence: 99%
“…Early in our IL studies, we applied protic ILs for use as H + -conducting electrolytes for non-humidified H 2 /O 2 fuel cells operating at temperatures greater than 100°C based on the expectations that cations having active protons (typically ammonium cations) are highly mobile and electrochemically active for use in fuel cell reactions, i.e., the hydrogen oxidation reaction (HOR) and oxygen reduction reaction (ORR). 43,44 In the case of acidic aqueous systems (including polymer electrolyte membrane fuel cells), water molecules act as a base, accepting protons to form hydronium cations (H 3 O + ). H + can be conducted through such media by the migration of H 3 O + cations themselves or by proton exchange between H 3 O + and H 2 O, the so-called vehicle and Grotthuss mechanisms, respectively.…”
Section: H © -Conducting Protic Ils and Fuel Cellsmentioning
confidence: 99%
“…45 Our initial interest in H + -conducting electrolytes concerned the transport properties of H + in protic ILs. [43][44][45][46][47] At that time, K.-D. Kreuer at the Max Planck Institute for Solid State Research was carrying out pioneering research with non-aqueous proton carriers; [48][49][50][51] his research focused on the autoprotolysis reactions of neutral species such as imidazole and pyrazole, which form proton defects in the systems and accelerate Grotthuss transport. The remarkable changes in conductivity that occur on changing the composition of systems of imidazole or pyrazole and H 2 SO 4 opened a new route to the design of non-aqueous proton conductors.…”
Section: H © -Conducting Protic Ils and Fuel Cellsmentioning
confidence: 99%
See 2 more Smart Citations